Oral Malignant Melanoma of Right Mandibular Gingiva in Dog: Case Report - Thermtong, Puttipong; Poodee, Poosuda; Kunchornwichai, Wanatchaporn; Plianprasert, Sarobol; Laoharatchatathanin, Titaree (Journal of Mahanakorn Veterinary Medicine, 2022)
A 12-year-old neuter male Mixed dog, presented with a mass of right mandibular gingiva for 2 month (size 4x5 centimeter). Previously, that used to have surgery for oral malignant melanoma, out from the right mandibular area approximately 1 year. Overall results from the general physical examination were normal unless enlargement of right submandibular lymph node, left submandibular lymph node and right popliteal lymph node. The histopathological diagnosis was oral malignant melanoma and metastasis into right submandibular lymph node. The dog was prescribed with the total right hemimandibulectomy and postoperative chemotherapy which included Lomustine (CCNU) for a 25 week treatment duration. The results after chemotherapy showed the lymph nodes decreased in size and revealed no recurrence in nearby areas. A thoracic radiograph and an abdominal ultrasound did not reveal evidence of metastasis when compared to pre chemotherapy.